A terceirização do trabalho da(o) psicólogo(a) na política de assistência social - Brandolt, Catheline Rubim (2019)
Outsourcing, as a strategy adopted in the Public Administration, advances in the field of Public Policy. The policy of Social Assistance coexists intensely with reduction, weakening and precariousness of investments, mechanisms through which the Outsourcing operates. This study aims to analyze the Outsourcing of the professional practice of Psychology in Social Assistance Policy in a municipality in the interior of Rio Grande do Sul / RS. The data were organized in scientific articles format. The first article consists of a study about the academic production of Psychology on the theme of Outsourcing. For this, a systematic review was used with consultation to the scientific databases. This construct made it possible to analyze that this theme is still little explored by the profession, even though it is one of the ways of work in permanent expansion in Brazil. The second and third studies result from the analysis of the information collected with the 12 psychologists who worked in the social assistance services, through a contract outsourced, in the last five years. The information collection took place through semi-structured interviews, which were analyzed qualitatively according to the content analysis. The results presented and discussed in these articles identify the relationships and working conditions and the performance of the functions and activities performed by the professionals as aspects of the precariousness of work, potentialized by Outsourcing, in the Social Welfare Services. Thereby, it can be concluded that the outsourced contracts of the psychologists, enhance the precariousness and exploitation of the worker, exposing them to relationships based on fear and intimidation, the constant sensation of: insecurity, instability and devaluation, as well as manifestations of illness resulting from work. Therefore, this reveals the perverse nature of outsourcing, which involves the work, social and personal dimensions of the workers.